PENGEMBANGAN FASILITAS DI AIR PANAS SUAMAN KABUPATEN ROKAN HULU PROVINSI RIAU - Praja, Zuri Agba; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Facility is very important for a tourist attraction, which is to fulfill the wishes of visitors so that visitors feel comfortable and happy while in the tourist attraction, so as to increase tourist arrivals in the tourist attraction. The reseacrh aims to determine the expansion of existing facilities The Hot Suaman Rokan Hulu Riau Province.This study used a descriptive quantitative method to examine problems in the lift. The samples in this study were 100 respondents, who were taken by using accidental sampling. While data collection techniques in this study using observation, questioner, and interviews. By using a Likert scale as a measure to determine the length of the short interval. With sub-variables on tourism facilities (Spiliane, 1994) is divided into the main facilities, support facilities, and supporting facilities.From the results of research conducted in the field of research on the development of facilities in Hot Suaman Rokan Hulu Riau Province, with the theory of the development of facilities that is divided in three sub-variables, namely, the main facility, support facilities, and supporting facilities, it results in the field can namely Development of facilities in Hot Suaman Rokan Hulu Riau Province included in the category quite well.Keywords : Tourism Facilities, Attractions, Rokan Hulu